Access to Health Information: a Key for Better Health in the Knowledge Society - Geissbuhler, A. (Yearbook of Medical Informatics, 2008)
Objectives To illustrate how access to health information is a key determinant to the strengthening of health and healthcare systems, and highlight related current challenges of the evolving knowledge society.MethodsReflections on some of the dimensions of access to health information, with a focus on current evolutions of the World-Wide-Web, unresolved issues and research perspectives.Conclusion Our knowledge society is growing, maturing, and bringing powerful tools that can improve the quality, safety, and efficiency of healthcare processes and help citizens manage their health. However, many obstacles and challenges are still facing us. These include our ability to manage information and knowledge rather than data, produce decision-support tools with contents and ergonomics that effectively change behaviors, orient information users in the ever-growing jungle of the social World-Wide-Web, learn how to make sense and enable knowledge discovery in the huge and increasingly connected biomedical data repositories, and bridge the digital divides that exist within communities and across the world.
Keywords: Information society; information retrieval; social web; semantic web; globalization; patient empowerment